2020
DOI: 10.1186/s12893-020-00864-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary mature cystic teratoma of the lung: case report of a rare entity

Abstract: Background Intrapulmonary teratoma (IPT) is a rare type of extra gonadal teratoma which often presents with non-specific symptoms and can be misdiagnosed as other diseases. Here we report a patient with IPT which was initially misdiagnosed as lung hydatid cyst versus abscess. Case presentation We report an intrapulmonary teratoma in a 27-year-old female presenting with persistent chest pain and dyspnea since a few years prior to her admission with associated symptoms of cough and fever. Chest x-ray only show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…Other symptoms reported in the literature include trichophytic, pneumonia, fever, bronchiectasis, abscesses, and infection (8). The size of the neoplasm is not related to malignancy (7,8). Reports of various studies have shown that laboratory tests are generally unremarkable (9,10), which is concordant with our case.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Other symptoms reported in the literature include trichophytic, pneumonia, fever, bronchiectasis, abscesses, and infection (8). The size of the neoplasm is not related to malignancy (7,8). Reports of various studies have shown that laboratory tests are generally unremarkable (9,10), which is concordant with our case.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that a lobulated cystic lesion with peripheral translucency is distinctive for the diagnosis of teratoma on CT, as in our case, though having such specific features as peripheral calcification or translucency; our clinicians missed the differential diagnosis of teratoma, which is due to the lack of information and rarity of the lesion. The commonly mentioned preoperative differential diagnoses are lung abscess and hydatid cyst (8). In our case, the preoperative chest X-ray and CT scan resulted in the misdiagnosis of a lung abscess, after which the patient was treated with a broad-spectrum antibiotic.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Nonetheless, the results may occasionally demonstrate non-specific findings. In cases where malignancy is suspected, further studies, such as an MRI of the chest or PET-CT, may be required to establish a definitive diagnosis [ 5 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hydatid cysts typically affect the lower lobes, with a preference for the right basal lobe. Cystic teratomas and hydatid cysts may mimic each other and distinguishing between the two requires careful interpretation of the patient’s clinical context, serological data, and radiographic imaging, with CT and MRI being the most useful modalities for detecting pulmonary cysts and their complications [ 4 , 8 , 12 ]. In our case, MRI was the most accurate imaging modality, showing elements of fat and other characteristics of cystic teratoma, such as intraparenchymal infiltration and direct bronchial connection, which is a distinguishing feature of intrapulmonary teratoma.…”
Section: Discussionmentioning
confidence: 99%